ROLE OF WOMEN IN SOCIETY - Nizamova Feruza Alimullaevna (Western European Studies, 2024)
Among the problems and tasks of national and national importance, the most important topic of which is presented in every speech of our country's president is aimed at improving the system of protection of legal, social, economic and spiritual interests of women in the family, state and society. Using the right granted by the Constitution, women are taking an important place in the Republic of Uzbekistan in the management of the state and society
Keywords: important; state; Uzbekistan; society